Analysis of IDF Illocutionary Speech Acts and Masafer Yatta Residents in the Film No Other Land: Analisis Tindak Tutur Ilokusi IDF dan Penduduk Masafer Yatta dalam Film No Other Land - Reza, Reza Ulil Albab (Universitas Muhammadiyah Sidoarjo, 2025)
No Other Land is a film with a message of peace to the world about the humanitarian conflict between the Israeli Defence Forces (IDF) and the residents of Masafer Yatta in Palestine. The film records the five-year journey of the Masafer Yatta residents against the IDF until they were expelled from their hometown. This study aims to determine the form of illocutionary speech acts during the five years between the IDF and the residents of Masafer Yatta recorded in the film No Other Land. This study uses a qualitative approach by collecting data through dialogue transcripts in film scenes showing the interaction of the IDF with the residents of Masafer Yatta and analyzing them using John Searle's illocutionary speech acts. The study found 63 illocutionary speech acts. 30 utterances from the IDF in the form of 20 directives, 8 declaratives, and 2 commissives. While 33 utterances from the Masafer Yatta community consist of 15 assertives, 11 expressives, 2 commissives, 2 declaratives, and 3 directives. IDF utterances are dominated by directive and declarative speech acts to control and shape legal reality. In contrast, the Masafer Yatta community predominantly uses assertive and expressive speech acts as symbolic resistance to assert their existence, history, and right to life.